The Relationship Between Peer Conformity and Bullying Behavior in Middle School Students - Lailatus Sholihah; Riza Noviana Khoirunnisa (Universitas Negeri Surabaya, 2023)
This research is motivated by the rise of cases of bullying behavior in adolescents, one of the causes of which is peer conformity, especially at school. The purpose of this study was to find out whether there is a relationship between peer conformity and bullying behavior of junior high school students, the research location is SMP Negeri 2 Puri Mojokerto. The respondents used were class VII and VIII with a total sample of 158 students. This research method is quantitative with saturated sampling technique using SPSS 17.0 for Windows. The instrument used is the conformity scale and bullying behavior using a questionnaire. In this analysis using the Product Moment Correlation Analysis formula using SPSS 17.0 for windows, the researcher conducted an analysis test on 158 students with a result of 0.000 which was significantly less than 0.05 or p<0,05. Hypothesis testing produces a correlation coefficient of -0.363 between the variables of conformity and bullying behavior, to test the hypothesis using Pearson's Product Moment, showing a low negative correlation between the x and y variables. So there is a significant relationship between peer conformity and student bullying behavior so that it has a negative but low correlation. Key word : Conformity, Bullying behavior